6x-7(1-x)-(10x+4)=0

Simple and best practice solution for 6x-7(1-x)-(10x+4)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-7(1-x)-(10x+4)=0 equation:


Simplifying
6x + -7(1 + -1x) + -1(10x + 4) = 0
6x + (1 * -7 + -1x * -7) + -1(10x + 4) = 0
6x + (-7 + 7x) + -1(10x + 4) = 0

Reorder the terms:
6x + -7 + 7x + -1(4 + 10x) = 0
6x + -7 + 7x + (4 * -1 + 10x * -1) = 0
6x + -7 + 7x + (-4 + -10x) = 0

Reorder the terms:
-7 + -4 + 6x + 7x + -10x = 0

Combine like terms: -7 + -4 = -11
-11 + 6x + 7x + -10x = 0

Combine like terms: 6x + 7x = 13x
-11 + 13x + -10x = 0

Combine like terms: 13x + -10x = 3x
-11 + 3x = 0

Solving
-11 + 3x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '11' to each side of the equation.
-11 + 11 + 3x = 0 + 11

Combine like terms: -11 + 11 = 0
0 + 3x = 0 + 11
3x = 0 + 11

Combine like terms: 0 + 11 = 11
3x = 11

Divide each side by '3'.
x = 3.666666667

Simplifying
x = 3.666666667

See similar equations:

| 5(6x+4)-4(3x-8)= | | 3(m-5)=-6 | | 49.2(x+4.1)=x | | 1.2(x+1.3)=2.4 | | 5x^5y^8+15x^2y^3= | | 3(m+0.5)=-2.1 | | 4(s+2)=4 | | 3/4(x-8)=71/2 | | 2x+24= | | 2x-3(4-x)=5+4(2x+1) | | -7-3x=-2x | | x+3/5=4/7 | | 4c^2d^6-7c^2d^6= | | 0.4(x+2.2)=5.4 | | x^2+5x-5=0 | | 5+2(3Y-1)=7Y+6 | | x+3/5=2/3 | | 2x-3=14x | | 6x^4-7x^3+8x^2-7x+2=0 | | 1.4-3=2+h | | x^4+2x+2=0 | | 0.3(k-0.2)=0.6 | | 5x^2-4x-2=0 | | 12+3x=x | | 8x^3+6x^2-5x+1=0 | | 140-7x=29x+16 | | 2x-9=x | | -3x-1-5x+4= | | t^2=3t+7 | | 9-7x=108-28x | | 9-2x=x | | 6+5x=x |

Equations solver categories